Association of obesogenic environment and hedonic appetite with chronic fatigue in Turkish adults - Helvacı, Gizem; Tayhan, Fatma (Frontiers in Nutrition, 2025)
BackgroundChronic fatigue is a persistent state of physical, emotional, and cognitive exhaustion that does not resolve with rest. Behavioral and environmental factors may contribute to the onset and course of chronic fatigue. In this context, we aimed to examine the predictive roles of obesogenic environment and hedonic appetite in chronic fatigue.MethodWe conducted the study on 505 Turkish adults aged 18–65. Participants completed a questionnaire form containing questions about demographic characteristics, dietary habits, the Chalder Fatigue Scale (CFS), the Power of Food Scale (PFS), and the Assessment of Obesogenic Environment Assessment Scale (AOES).ResultsThe proportion of women is higher in the third tertile (highest fatigue) than in the first tertile (p = 0.014). The proportion of those who exercise regularly in the third tertile is lower compared to the first and second tertiles (p = 0.001). The percentage of participants who are sedentary for more than 4 h per day is lower in the first tertile than in the second and third tertiles (p = 0.007). The proportion of individuals who often eat in front of a screen is higher in the third tertile (41.2%) than in the first tertile (27.2%; p = 0.016). The proportion of individuals in the first tertile of fatigue level who prefer fast food when eating out is 44.5%, which is lower than that of the second and third tertiles (p < 0.05). As hedonic appetite (β = 0.370, p < 0.001) and exposure to obesogenic environment (β = 0.131, p = 0.002) levels increase, fatigue symptoms also increase. It was found that individuals with high levels of chronic fatigue had a more obesogenic environment in terms of physical, social, and economic aspects; however, they were environmentally advantaged in terms of cultural factors and access to experts (p < 0.05). Participants who self-report having a regular sleep schedule exhibit significantly lower levels of fatigue (β = −0.146, p < 0.001).ConclusionOur findings show that obesogenic environments, irregular sleep schedules, and hedonic appetite are associated with fatigue perception and may serve as its predictors. Strategies to improve physical, social, and economic aspects of obesogenic environments may help prevent chronic fatigue, while addressing hedonic appetite through psychotherapy could also be beneficial. Effective prevention and management of chronic fatigue can strengthen long-term societal resilience and support overall wellbeing.